Nusantara Interaction The Case of Joget as a Trans-Cultural Entertainment - Parani, Julianti (Paradigma: Jurnal Kajian Budaya, 2018)
The focus of discussion in this paper is joget as a dance which embodies the concept of Nusantara (Indonesian archipelago), which has undergone much development from the past to the present. Beginning as an entertaining social dance in various Southeast Asian countries, joget became a customary form of entertainment in the whole context of Nusantara as a region. Surprisingly, it has also inspired new genres and types of traditional dances for centuries. Around 1920s to 1930s, it was the most popular form of dance in many halls of entertainment in Indonesia, Singapore, and the Malay Peninsula. Joget was the most common type of social dance. It has an indigenous origin, but gained popularity in urban setting at the time when ballroom and Latin-American dances were not yet popular.